2008
DOI: 10.1103/physrevlett.100.117207
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Magnetization Direction in Molecules via Their Oxidation State

Abstract: By means of ab initio calculations we predict that it is possible to manipulate the magnetization direction in organic magnetic molecules by changing their oxidation state. We demonstrate this novel effect on the Eu 2 C 8 H 8 3 molecule, in which the hybridization of the outer ring states with the Eu 4f states causes a redistribution of the orbitals around the Fermi level leading to a strong ferromagnetism due to a hole-mediated exchange mechanism. As a key result, we predict an oscillatory behavior of the eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
70
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 24 publications
3
70
1
1
Order By: Relevance
“…With respect to bulk molecular crystals, the planar and open coordination structure of the self-assembled Fe array makes such a system extremely sensitive to chemisorption, providing straightforward control of the preferred Fe spin orientation. Through the analysis of the XAS and XMCD spectra, we can further identify the cause for the easy-axis switch in the metal-organic complexes, revealing a different mechanism from the one proposed by Atodiresei and co-workers 18 based on the control of the metal oxidation state. Our calculations show that only the ligand field is affected by O 2 adsorption, whereas the formal Fe oxidation does not change.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…With respect to bulk molecular crystals, the planar and open coordination structure of the self-assembled Fe array makes such a system extremely sensitive to chemisorption, providing straightforward control of the preferred Fe spin orientation. Through the analysis of the XAS and XMCD spectra, we can further identify the cause for the easy-axis switch in the metal-organic complexes, revealing a different mechanism from the one proposed by Atodiresei and co-workers 18 based on the control of the metal oxidation state. Our calculations show that only the ligand field is affected by O 2 adsorption, whereas the formal Fe oxidation does not change.…”
mentioning
confidence: 79%
“…Recent studies showed that the magnetization direction of surface-supported paramagnetic molecules can be controlled through exchange coupling with a magnetic film, which provides robust ferromagnetic properties but does not enable each molecule to be switched independently from the substrate or its neighbours 16,17 . Alternatively, theoretical work suggested that the sign of magnetic anisotropy could be reversed in metal-organic complexes by exploiting oxidation processes that affect the hybridization of molecular orbitals with metal states carrying non-zero orbital magnetization 18 . Here, we investigate supramolecular self-assembly on a non-magnetic Cu surface as a means to produce two-dimensional (2D) arrays of regularly spaced Fe spins, the magnitude and magnetic anisotropy of which are manipulated by lateral and axial molecular ligands.…”
mentioning
confidence: 99%
“…The ultimate goal of this approach is to construct devices in which the adsorbed organic molecules on surfaces are the main functional units. 1 Among the advantages of using molecules in future electronic devices, it is worth mentioning the possibility of designing such devices at a molecular scale to construct organic field-effect transistors [2][3][4] or ultrahigh-density memory circuits. 5 A promising way to manufacture a molecular electronic device is to use self-assembled monolayers ͑SAM͒ 6 adsorbed on a specific substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the calculated moleculeferromagnetic surface systems can be understood as following: (i) although having a low reactivity, Bz (C 6 H 6 ) is an aromatic 6π-electron system [13] that can form sandwich type compounds with d-metals [14] and chemisorbs on reactive surfaces [15,16]; (ii) a high-reactive 5π-electron system, Cp (C 5 H 5 ) strongly interacts with dmetals and forms an aromatic 6π-electron system in sandwich type molecules like ferrocene [13]. However, Cp can be brought on the surface by decomposition of the ferrocene molecule which occurs after its adsorption on metallic surfaces [17]; (iii) an 8π-electron system, Cot (C 8 H 8 ), binds strongly the metal atoms by forming an aromatic 10π-electron system [13] and is well known to react even with f -electrons of rare earth metals [18,19] forming sandwich type molecules and long nanowires [20].…”
mentioning
confidence: 99%